New Advances on Nutrients Recovery from Agro-Industrial and Livestock Wastes for Sustainable Farming - Mirko Cucina (MDPI AG, 2021)
The world’s population continues to rise, with a medium-variant forecast predicting that by 2050, the global population will have surpassed 10 billion people [1] [...]